Resistance of Red Light District Communities in Responding Dolly Closure Policy in Surabaya City Indonesia - Daulay, Pardamean (Advances in Social Sciences Research Journal, 2018)
This paper discusses red light district community resistance after the closure of Dolly red light district which focused on the causes and forms of resistance carried out. This study used a qualitative approach with a case study in Dolly and Jarak as red light districts of Surabaya - Indonesia. The results of this study indicate economic mastery is a very important variable as a cause of resistance as well as a determinant of the resistance form made. Forms of resistance can be classified into three, namely; open resistance, symbolic resistance, and covert resistance. The form of covert resistance is far more dangerous because it can enter the wider community. The practice of covert prostitution has so far not been considered a resistance, but the strategy of surviving in the middle of the social space of the former Dolly red light district that is changing.